MODERNIZATION OF THE ISLAMIC CURRICULUM; CREATING A BALANCE BETWEEN TRADITION AND INNOVATION FOR FUTURE GENERATIONS - Fatimah, Siti; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze and study the Modernization of the Islamic Curriculum, realizing a balance between tradition and innovation for future generations. This research was conducted at the Miftahul Arifin Islamic Boarding School in the Bantara Probolinggo area, East Java Province. Researchers used a qualitative case study type approach. Data was collected using interviews, observation, and documentation techniques and then analyzed in several steps: data collection, data reduction, data presentation, and conclusions. The research results show that there is a profoundly interdisciplinary approach, which does not only focus on academic learning but also on developing the character and social skills of students. In addition, a curriculum model based on local wisdom is implemented to ensure the curriculum remains relevant to the local social and cultural context, strengthening the Islamic boarding school's identity and its contribution to preserving local culture. A community-based pedagogical approach is also applied to connect students with the surrounding community, enriching their learning experience through social and cultural engagement. Research findings show that this combination of techniques can form students who understand religion, are ready to face global challenges, and make positive contributions to society.